Left ventricular pseudoaneurysm perceived as a left lung mass - Yaliniz, Hafize; Demir, Serafettin; Gocen, Ugur; Atalay, Atakan; Salih, Orhan Kemal (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Left ventricular pseudoaneurysm is a rare complication of aneurysmectomy. We present a case of a surgically treated left ventricular pseudoaneurysm, which was diagnosed three years after coronary artery bypass grafting and left ventricular aneurysmectomy. The presenting symptoms, diagnostic evaluation, and surgical repair are described.